Water Pollution in Coastal Communities in Indonesian: A Review - Siti Nurfadilah H; Nurmiaty Hamzah; Widarni (Journal of Epidemiology and Health Science, 2025)
Background: Water pollution in coastal areas poses both direct and indirect threats to public health. Exposure to contaminated water can lead to various illnesses, including gastrointestinal disorders, dermatological infections, and respiratory diseases resulting from the inhalation of toxic gases or pollutant particles. Moreover, the consumption of fish or seafood contaminated with hazardous substances may result in the bioaccumulation of toxic elements in the human body, increasing the risk of chronic conditions such as liver damage, kidney dysfunction, and neurological disorders. Objectives: This study aims to explore the relationship between coastal water pollution and public health outcomes in order to support the development of more effective policies and strategies for sustainable coastal environmental management. Method: This research is a literature review intended to identify and synthesize findings from relevant national and international journal articles. Literature sources were retrieved using Google Scholar, employing keywords such as "water pollution," "coastal communities," "environmental health," "water quality," and "water-based diseases." Results: The review indicates that coastal areas hold significant ecological and economic importance but are increasingly threatened by severe water pollution. Major sources of pollution include industrial discharge, agricultural runoff, and untreated domestic wastewater. The public health consequences are considerable and include a heightened incidence of waterborne diseases such as diarrhea, cholera, hepatitis A, and skin infections, along with long-term health risks associated with exposure to heavy metals and toxic chemicals. From an environmental perspective, pollution contributes to the degradation of aquatic ecosystems, loss of biodiversity, and eutrophication caused by nutrient over-enrichment. Conclusion: Based on the reviewed literature, it can be concluded that pollution from domestic, industrial, and agricultural sources significantly deteriorates the quality of coastal waters. The resulting health impacts range from acute waterborne diseases to chronic respiratory and systemic disorders due to heavy metal toxicity. To mitigate these effects, comprehensive management strategies are essential. These include the improvement of sanitation infrastructure, the implementation of stricter regulatory frameworks, and the promotion of community awareness and education to support sustainable, long-term solutions. Keywords: Water Pollution, Environmental Health, Water Quality, Sanitation, Coastal Communities.